EVALUASI MUTU FISIK DAN UJI IRITASI KOSMETIKA LULUR DENGAN MEMANFAATKAN BONGGOL NANAS SEBAGAI BAHAN AKTIF - Suhartini; Tansri, Suhartini; Bintoro, Rina; Nurhidayat (Jurnal Kesehatan Yamasi Makassar, 2025)
The pineapple variety used in this research was queen pineapple. Pineapple processing produces waste in the form of pineapple tubers. The aim of this research is to make cosmetic scrubs with the active ingredient queen variety pineapple weevil (Ananas cosmosus L) and to determine the results of physical quality tests and determine the safety/irritation of body scrub preparations from pineapple weevils. This scrub preparation is made with three formulas using different concentrations of pineapple weevil powder, namely 5%, 7% and 9%. Physical quality tests of scrub preparations include organoleptic tests, homogeneity tests, pH tests and spreadability tests. Based on the results of the physical quality test, it shows that the formula with a pineapple weevil active substance concentration of 5% and the formula with a pineapple weevil active substance concentration of 7% is a formula that meets the physical quality test standards. Irritation/safety tests were carried out on rabbits and showed that the scrub preparation did not cause irritation, the degree index produced for all preparations tested was 0 (no irritation)